2020
DOI: 10.2298/tsci190118169d
|View full text |Cite
|
Sign up to set email alerts
|

Ignition and combustion characteristics of wall-impinged kerosene (RP-3) fuel spray with varying injection parameters

Abstract: The fuel quantity and injection pressure are two essential factors to optimize the injection strategy. In this paper, we focus on the investigation for the ignition and combustion characteristics of wall-impinged kerosene (RP-3) fuel spray at different injection quantities and pressures. Experiments are conducted in a constant volume combustion vessel to simulate the Diesel engine condition, adopting a single-hole nozzle with 0.22 mm. The flame images are captured using a high-speed camera, and then the behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Therefore, it is crucial to investigate the spray characteristics of the pressure swirl nozzle at low flow rates to understand the ignition performance of the auxiliary power device and enhance aviation engine safety [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is crucial to investigate the spray characteristics of the pressure swirl nozzle at low flow rates to understand the ignition performance of the auxiliary power device and enhance aviation engine safety [2] .…”
Section: Introductionmentioning
confidence: 99%
“…They found that the rotation mode in the swirl flame is primary under stable conditions, while three modes of the flame dynamics, including vibration, rotation, and flame shedding, can be found at near-lean blowout conditions. Du et al [24] examined the ignition performance of RP-3 spray under wall-impinged conditions. They found that a low temperature wall will prolong the spray ignition delay, but a low injection pressure at small injection quantities can shortening the ignition delay.…”
Section: Introductionmentioning
confidence: 99%